Relationship between cricket participation, health and well-being: scoping review protocol - Nigel K Arden; Garrett Scott Bullock; Nirmala K Panagodage-Perera; Stephanie R Filbay (BMJ Open)
Introduction Cricket is a popular sport played by 2.5 billion people of all ages and abilities. However, cricket participation is decreasing in the UK, despite an increased focus of governments on increasing sport participation to enhance public health. Understanding the health benefits and mitigating the health risks of cricket participation may help cricket organisations promote cricket participation while optimising the long-term health of cricket participants. Currently, there is no literature review on the relationship between cricket participation, health and well-being; thus, this relationship remains unclear. Therefore, the aims of this scoping review were (1) to investigate the relationship between cricket participation, health and well-being and (ii) to identify the research gaps related to cricket, health and well-being.Methods and analysis Due to the broad nature of our research question and the large number of health outcomes assessed within the cricket literature and to facilitate identification of research gaps, a scoping review methodology was used. The methodology of this paper was informed by previous scoping review protocols and best practice methodological frameworks. MEDLINE, CINAHL, Embase, Scopus, PsycINFO, SPORTDiscus, Cochrane Library, EBSCO, Web of Science and PEDro and grey literature sources (Google Scholar, ClinicalTrials.gov, ISRCTN Registry and ProQuest) will be systematically searched. Studies that assess a construct related to health and/or well-being in current and/or former cricketers from all ages and standards of play will be eligible. Two reviewers will independently screen full texts of identiﬁed studies for eligibility and will perform data extraction. Results will be presented in tabular and graphical forms and will be reported descriptively.Ethics and dissemination This research is exempt from ethics approval due to the data being available through published and public available resources. Results will be published in a peer-reviewed sports and exercise medicine journal regardless of positive or negative findings. In addition, results will be disseminated through multiple platforms, including conference presentations and social media using multimedia resources (eg, infographics, animations, videos, podcasts and blogs), to engage stakeholder groups, including cricketers, cricket coaches, sporting bodies, sports medicine professionals and policy makers. There findings will inform clinical decision making, policy changes and future research agendas.